A fuzzing‐based test‐creation approach for evaluating digital TV receivers via transport streams. (2nd October 2022) - Izumi, Fabricio; de Lima Filho, Eddie B.; Cordeiro, Lucas C.; Maia, Orlewilson; Fabrício, Rômulo; Farias, Bruno; Silva, Aguinaldo
Abstract: Digital TV (DTV) receivers are usually submitted to testing systems for conformity and robustness assessment, and their approval implies correct operation under a given DTV specification protocol. However, many broadcasters inadvertently misconfigure their devices and transmit the wrong information concerning data structures and protocol format. Since most receivers were not designed to operate under such conditions, malfunction and incorrect behaviour may be noticed, often recognized as field problems, thus compromising a given system's operation. Moreover, the way those problems are usually introduced in DTV signals presents some randomness, but with known restrictions given by the underlying transport protocols used in DTV systems, which resembles fuzzing techniques. Indeed, everything may happen since any deviation can incur problems, depending on each specific implementation. This error scenario is addressed here, and a novel receiver robustness evaluation methodology based on non‐compliance tests using grammar‐based guided fuzzing is proposed. In particular, devices are submitted to unforeseen conditions and incorrect configuration. They are created with guided fuzzing based on real problems, protocol structure, and system architecture to provide resources for handling them, thus ensuring correct operation. Experiments using such a fuzzing scheme have shown its efficacy and provided opportunities to improve robustness regarding commercial DTV platforms. Abstract : Although the present work was focused on DTV networks, there is a myriad of different broadcasting systems that can benefit from it as long as they rely on configuration data sent in their protocol structures.